Siedlungswüstungen in Westgrönland - Becker, Hans (ERDKUNDE, 1975)
Desertions from Viking times, from the 18th/19th centu ries and the recent desertions of the 20th century in Western Greenland have been studies and the reasons and extent of the desertions are discussed. Following this an attempt is made to draw out general rules and results from compara tive study of the individual, temporally-separated desertion waves which could be typical of the desertion phenomenon on the polar edge of the Oecumene. Amongst other things, it is argued that there are reasons for desertion processes in this part of the world which are relatively unimportant in other areas of the inhabited earth. Of particular rele vance is the dependence of desertions on economic circum stances. The inclusion of the Western Greenland settlement area in large supra-regional economic relationships ob viously played a decisive role in all the periods studied.